“Crianças estilosas” : imagens de infância nas redes sociais - Valério Júnior, Itamar José (2016)
This research aims to analyze the speeches of beauty and seduction that make up the images of female children in social networks, especially Facebook on the page "Stylish Children - Personal Blog". Media and communication technologies are highlighted in contemporary society, promoting constant changes in human relationships and in the subjective constitution processes. In this context, we have the childhood intertwined with digital media. The main research questions are: what childhood images are reflected in digital mirrors present in the social network and how these are contemporary discourses around of the timefile that present as cultural pedagogies teaching to the children ways of being, behaving and relate to each other? What are the discourses present in social pages where girls images are associated with beauty and seduction? What values and social perspectives cross the images of girls bodies posted on Facebook in the page "Stylish Children - Personal Blog"? The methodology in this research it is imprint by qualitative approach with theoretical and methodological and analytical contributions of Mikhail Bakhtin, with highlight to the concepts of utterance, dialogism and polyphony. The focus of analysis is the page "Stylish Children - Personal Blog," on the Facebook. This blog was selected for having the greatest number of likes (56.444) until April 30, 2015, among the other pages that bring childhood representations in images of children, with speeches of beauty and seduction. The decision to work only with the girls pictures gave up due to these being the majority. Children in this page have ages ranging from a few months (babies) up to seven years old, mostly of them white ethnicity. The images of these girls stand out not only because they are just photos, but also the ways these photographs are represented, revealing ambiguous elements, interweaving innocence with seduction. We observed in this research that although we noted the presence of the in social networks, not all imagetic discourses related to childhood are produced by themselves, but by adults. The analyzed images are the result of the discourses of another, more specifically, the adults discourses, in a tense process of childhood idealization. The imagistic speeches, referring to the beauty and seduction, invested in the bodies of the girls, have echoes that circulate in the fields of education, sexuality and gender relations. They are speeches that transiting in our culture and embrace thus contemporary childhood.